ANALISIS FORECASTING LINIEAR PROGRAMING UNTUK OPTIMALISASI JUMLAH PRODUKSI PT UNILEVER INDONESIA.Tbk - Niken Kelasworo; Siti Marliah; Narita Risdianovi (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
PT Unilever Indonesia Tbk (UI) which carries the Wall's brand. The company has been doing its best to run its business in optimizing the number of units of production to meet demand and income, but still not successful, especially the remaining raw materials. The purpose of this study is to provide a production optimization solution using forecasting and linear programs. The results of this study resulted in the most appropriate forecasting method for ice cream in the period of December 2016 was the trend analysis method and linear programming method, the optimal production number for the December 2016 period with QM for Windows 2 was as much as Paddle Pop ice cream. 19,171,340 units and Cornetto ice cream of 4,971,443 units. And the total profit that the company will get in December 2016 is Rp. 694,226,260.77.